2012
DOI: 10.1002/bio.2376
|View full text |Cite
|
Sign up to set email alerts
|

Flow injection chemiluminescence determination of 2‐methoxyestradiol based on inhibition of luminol‐potassium ferricyanide reaction

Abstract: A novel flow-injection chemiluminescence (FI-CL) method is described for the determination of 2-methoxyestradiol (2-ME). The method is based on the inhibitory effect of 2-ME on the CL reaction of luminol and potassium ferricyanide in alkaline solution. Under optimal conditions, net CL intensity was proportional to 2-ME concentration in synthetic and mouse plasma samples. Corresponding linear regression equations were 8.0 x 10(-9) -1.0 x 10(-7) g/mL for synthetic samples and 2.0 x 10(-9) -1.0 x 10(-7) g/mL for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…Moreover, the absorption intensities of λ 302 and λ 420 for K 3 Fe(CN) 6 were obviously decreased. It could be demonstrated that the light emitter of the CL system was the excited state of 3‐aminophthalhydrazide, which was in agreement with reports that the luminant of potassium ferricyanide with luminol was considered to be the excited state of 3‐aminophthalhydrazide ; the light emission emanating from relaxation of the excited state of 3‐aminophthalhydrazide then returned to ground state. Terbutaline sulfate could be oxidized by K 3 Fe(CN) 6 , and during this process produced active oxygen‐containing reactant intermediates, such as superoxide radical (·O 2 − ).…”
Section: Mechanismsupporting
confidence: 89%
“…Moreover, the absorption intensities of λ 302 and λ 420 for K 3 Fe(CN) 6 were obviously decreased. It could be demonstrated that the light emitter of the CL system was the excited state of 3‐aminophthalhydrazide, which was in agreement with reports that the luminant of potassium ferricyanide with luminol was considered to be the excited state of 3‐aminophthalhydrazide ; the light emission emanating from relaxation of the excited state of 3‐aminophthalhydrazide then returned to ground state. Terbutaline sulfate could be oxidized by K 3 Fe(CN) 6 , and during this process produced active oxygen‐containing reactant intermediates, such as superoxide radical (·O 2 − ).…”
Section: Mechanismsupporting
confidence: 89%
“…Nicotinamide contains an amido group, making it easily oxidized especially in alkaline solution. Therefore, the potential inhibitory mechanism of nicotinamide on the CL reaction on luminol and K 3 Fe(CN) 6 could be that the consumption of K 3 Fe(CN) 6 , which is the oxidant of luminol-K 3 Fe(CN) 6 system, led to a decrease in CL intensity 20,21 or nicotinamide acted as scavengers of luminol radicals like phenolic species of low reduction potential, 22,23 and then quenched the CL intensity.…”
Section: Possible Inhibition Mechanism Of CL Reactionmentioning
confidence: 99%
“…As a metabolite of 17-β estradiol, 2-methoxyoestradiol (2-ME) presents in the serum of women during the ovulatory which is a new anticancer drug (17) (Figure 1). Although several CL methods have been reported for the determination of 2-ME in pharmaceutical formulations and biological fluids (18)(19)(20), the proposed method is simple, highly sensitive and requires no special reagent. CL-based analytical methods show several advantages such as high sensitivity, simple operation and short analysis time.…”
Section: Introductionmentioning
confidence: 99%